The impact of high-intensity interval training on body composition handball athletes - Arifin, Mohammad Ikbar Shabiyan; Pamungkas, Hari; Nidomuddin, Muhammad; Yusuf, Havid; Saputro, Yulianto Dwi (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2024)
This research will review the impact of HIIT on the body composition of men's handball athletes and identify several factors. Was to evaluate the impact on body mass index (BMI), fat mass (FM), fat-free mass (FFM) and fat mass index (FMI) on the body composition of Malang City handball athletes. The subjects of this study were 14 men’s athletes, 21 years old, and received the same training program. Explains that the Paired T-Test of BMI is 0.003, Fat Mass is 0.004, Fat-Free Mass is 0.087, and Fat Mass Index is 0.000 because of the sig value. < 0,05. It can be interpreted that there is a significant effect on high-intensity interval training. The impact of high-intensity interval training has a significant impact on body mass index (BMI), fat mass (FM) and body mass index (BMI) on the body composition of handball athletes. The exercises performed have a positive impact on the formation of body composition, in the sport of handball, it takes a lot of explosive movements so ideal body conditions are very supportive of athlete performance. HIIT method is very useful in preparing training programs to form ideal body composition for coaches and the general public.